2021
DOI: 10.1111/liv.14824
|View full text |Cite
|
Sign up to set email alerts
|

HCV microelimination strategies: An interventional study in diagnosed patients without access to the system

Abstract: Hepatitis C virus (HCV) one-step diagnosis improves recovery in patients with active infection. However, patients with previous anti-HCV+ may be excluded. We aimed to identify and retrieve non-referred or lost-to-follow-up HCV-infected patients. All anti-HCV+ patients seen in our hospital between 2013 and 2018 were included.In the first phase, we identified anti-HCV+ patients who were not referred to the Gastroenterology Unit (GU) or lost-to-follow-up. In the second phase, recovered patients were invited for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…To achieve the goal set by the World Health Organization for HCV elimination, a diagnostic rate of 90% and a treatment coverage rate of 80% are required to achieve a 65% reduction in the rate of HCV-related deaths by 2030 [ 4 , 10 , 34 , 35 , 37 ]. A major challenge is determining the HCV genotype before initiating DAA regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the goal set by the World Health Organization for HCV elimination, a diagnostic rate of 90% and a treatment coverage rate of 80% are required to achieve a 65% reduction in the rate of HCV-related deaths by 2030 [ 4 , 10 , 34 , 35 , 37 ]. A major challenge is determining the HCV genotype before initiating DAA regimens.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have been reimbursed in Taiwan since 2017, and the government of Taiwan has set the goal of obtaining an 80% treatment coverage rate with DAAs by 2025 [ 1 , 7 , 8 , 9 ]. There are still several barriers to HCV elimination, such as the limitation of patient access to therapy, insufficient knowledge of HCV therapy, lack of awareness of the disease, and the complexity of treatment [ 4 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kracht et al 9 designed a retrieval project through screening prior HCV positive tests in Utrecht, Netherlands, where authors found that 14% of chronic HCV were LTFU but only 43% of the patients were re‐linked to HCV care. A study from Seville, Spain, analysed the anti‐HCV positive test results at the Microbiology Unit 5 . Of the total anti‐HCV‐positive patients, 21% were never referred to a specialist, and of those who were referred, 23.1% were LTFU.…”
Section: Discussionmentioning
confidence: 99%
“…LTFU occurs in all steps of the care cascade and may severely affect clinical outcomes. Studies from different countries have shown that approximately 14%–61% of patients diagnosed with HCV infection are LTFU 5–9 . This is likely the consequence of the slow, silent and asymptomatic progression of the disease, and prior experience with interferon (IFN)‐based therapy that had considerable side effects and low sustained virological response (SVR) rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation